IMPLEMENTASI MANAJEMEN KINERJA DI UNIKA SANTO THOMAS MEDAN - Tinambunan, Anitha Paulina (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
The management model of higher education institutions can be equated with a business model of higher education management services that must be managed professionally like other business institutions, but while still prioritizing academic quality as a "service product" that must be achieved. The performance management model is a framework that integrates how organizations set and align goals, eval_uate employee performance and encourage sustainable development. Since 2016 under the leadership of rector Dr. Frietz R. Tambunan, Unika Santo Thomas Medan has established a new performance management system with model from Armstrong & Baron because the starting point is changing the vision & mission in order to adapt to environmental changes. This means that there is a self-renewing cycle that explains the strategic goals of the organization with the goals of teams and individual employees. During the period of Prof. Sihol Situngkir (2020-2022), the Deming model was applied and utilized special software applications (LMS & SIAK) to simplify the performance management process (software based model). Rector Prof. Dr. Maidin Gultom SH, M.Hum uses the Torrington and Hall model. This can be seen from the existence of performance plans, monitoring from LPM and LPSI, regular eval_uations and awards at the end of the year and throughout the year. Performance management must be implemented to improve efficiency, effectiveness & employee productivity. Dr. Frietz R. Tambunan implemented the Performance for World Class Manufacturing (PWCM) system because it uses a new approach to quality by applying Total Quality Management (TQM) & a change in the way of managing employee with encouraging improved performance (Employee Involvement). Rector Prof. Sihol Situngkir implemented a Performance Measurement Questionnaire (PMQ) that resembles Behaviorally Anchored Rating Scales (BARS) by linking performance appraisals to certain behaviors that are considered important in the job. Rector Prof. Dr. Maidin Gultom SH, M.Hum implements a Balance Scorecard (BSC) which measures organizational performance in the aspect of customer satisfaction (the existence of a certificate 15021001 at Faculty of Economics and Business) and operational efficiency by conducting Benchmarking to Unika Atma Jaya Yogyakarta (UAJ) & Unika Parahyangan Bandung (UNPAR) and performance expectations expressed in continuous improvement targets such as the existence of an Sistem Penjamin Mutu Internal (SPMI) & implementing Ministry of Research, Technology and Higher Education Indonesia by engaging in MBKM (Merdeka Belajar Kampus Merdeka)